PENGARUH GOOD CORPORATE GOVERNANCE, UKURAN PERUSAHAAN, DAN KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN - Sugeng Raksono; Ricardo Suhendra Wirjawan (Universitas Budi Luhur, 2019)
The purpose of this research is to obtain empirical evidence about the effect of good corporate governance (managerial ownership, independent commissioner, audit committee, and board of commissioner), firm size, and financial performance which in this research measured by using financial ratio such as profitability, activity, solvability, and liquidity to firm value. Sample used in this research are all non financial companies listed in Indonesia Stock Exchange during the research period from 2015 until 2017. Sample selection method used is purposive sampling, in which 94 companies meet the criteria, resulting 282 data are taken as sample. Research data is analyzed by doing hypothesis test using multiple regression method to determine the model of research. The empirical evidence of this research indicated that audit committee, profitability, activity, and solvability affect firm value, while managerial ownership, independent commissioner, board of commissioner, firm size, and liquidity have no effect to firm value.